Elevated serotonin and 5‐HIAA in the brainstem and lower serotonin turnover in the prefrontal cortex of suicides. Issue 3 (23rd July 2013) - Bach, Helene; Huang, Yung‐Yu; Underwood, Mark D.; Dwork, Andrew J.; Mann, J. John; Arango, Victoria
<x xml:space="preserve">Abstract</x> Using high pressure liquid chromatography, we find more brainstem 5‐HT and 5‐HIAA in suicides compared with nonpsychiatric, sudden death controls throughout the rostrocaudal extent of the brainstem DRN and MRN. This suggests that 5‐HT synthesis in suicides is greater within all DRN subnuclei and the MRN compared with controls. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>